Employment Adjustments on the Internal and External Labour Market: An Empirical Study with Personnel Records of a German Company - Knut Gerlach; Olaf Hübler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Firms are affected by the product demand. This leads to employment adjustments. In the literature we find only very few contributions investigating the issue whether internal adjustments are linked and which relationships exist with external adjustments. Are they of a complementary or substitutive nature? Furthermore, it is of interest to find out, whether we can observe an obvious trend and whether the adjustments are driven by cyclical movements. For this study we have an extensive data set of a large German manufacturing company, which supplies innovative products for the domestic and international market, provided on a monthly base from January 1999 to December 2005. The empirical analysis starts with descriptive statistics. We find that the employment adjustment cycle coincides only to a certain degree with the macroeconomic cycle. Internal and external adjustments are more characterized by complementarity than by substitution. Over the observed period we cannot detect analogous wage adjustments. It is noticeable that in 2003 compared with the years before the number of employees is substantially reduced. The econometric investigation is based on a two-stage approach. We start with a bivariate probit estimation in order to extract the relationship between the probability of overtime and of promotion. Unobserved variables have opposite effects on the former and the latter adjustment instrument. Furthermore, we detect a negative trend of internal employment adjustments. Cyclical effects are ambiguous. The next step, the determination of external adjustments with respect to overtime and promotion adjustments, is split into two estimates. On the one hand we do not distinguish between the type of external employment adjustment and on the other hand we use this information separating between quits, layoffs, workers with a cancellation agreement and with a transition into a transfer organisation. The first approach demonstrates that a promotion reduces the probability to leave the firm while overtime is positively associated with an external job change. This pattern holds generally speaking in the second, more detailed estimates. Quits are the exception. In this case we observe opposite effects. Finally, we cannot detect any influences of promotions on cancellation agreements.
Keywords: J63; M51; 330; Personnel records; overtime; promotion; job mobility; cancellation agreement; transfer organisation; Personalbestand; Anpassung; Personalabbau; Wirtschaftliche Anpassung; Interner Arbeitsmarkt; Konjunktur; Deutschland